Climatic control on palaeohydrology and cyclical sediment distribution in the Plio-Quaternary deposits of the Guadix Basin (Betic Cordillera, Spain). (2nd December 2015) - Pla-Pueyo, Sila; Viseras, César; Candy, Ian; Soria, Jesús M.; García-García, Fernando; Schreve, Danielle
Abstract: A cyclical pattern can be observed in the central sector of the Guadix Basin (southern Spain) in the Late Pliocene-Quaternary alluvial fan deposits prograding into its axial valley. A climatic significance has been attributed to this cyclicity on the basis of sedimentological and preliminary isotopic studies. The progradation phases of the alluvial fans are here attributed to more arid time intervals in which the vegetation cover would be less developed, erosion and sediment supply would be higher, and base level would be lower. In contrast, the time intervals during which the fluvial system sediments dominated the area are inferred to be wetter and base level higher, with vegetation cover retaining the soils and preventing erosion. Permanent water supply to the river would therefore facilitate the aggradation of the floodplain and prevent progradation of the fans. Starting from a litho-, bio- and magnetostratigraphical frame provided for the area, an age is assigned to the alternation of the reddish sediments of the transverse alluvial fans and the greyish to white fluvio-lacustrine sediments of the axial drainage system. A cyclicity of ca. 100 ky has been identified in most of the alluvial fan progradation phases, falling within Milankovitch high-frequency eccentricity periodicities. Correlation of the phases with insolation curves is accordingly discussed as a possible origin for the cyclicity. Finally, the results offer new insights into early hominin occupation patterns in the region, through the identification of predictable resources of permanent fresh water that would have remained available throughout the recorded time span (that includes the Early–Middle Pleistocene transition) even during times of aridification.